THE ROLE OF DIGITAL HEALTH SERVICES AND TELEMEDICINE IN ECONOMIC DEVELOPMENT OF UKRAINE - Khilukha, Oksana; Riabkov, Serhii (Global Prosperity, 2026)
The study examines the digitalization of medical services and telemedicine as factors in Ukraine's economic development. Its relevance is determined by the growing importance of digital health infrastructure under conditions of health care reform, war-related disruptions, limited public resources, territorial disparities in access to care, and the need to preserve human capital. The objectives. of the study are to substantiate the macroeconomic role of digital medical services and identify the main channels through which digitalization affects the health care system, public finance, regional accessibility of care, and national economic resilience. The study is based on systemic, institutional, and economic approaches. The methods include analysis of scientific literature, regulatory documents, international policy materials, and Ukrainian evidence on e-Health, electronic prescriptions, electronic referrals, medical information systems, and telemedicine. The results demonstrate that the role of digital medical services extends beyond technological modernization. Digitalization reduces transaction costs by simplifying administrative procedures, improving patient routing, decreasing information asymmetry, and supporting more transparent management of medical services. e-Health infrastructure forms a data basis for budget planning, service monitoring, assessment of population needs, and more rational allocation of public resources. Conclusions. Telemedicine and digital communication channels improve access to care in rural, remote, and war-affected territories, reduce territorial barriers, and support continuity of medical assistance. Digital medical services may also preserve human capital by improving timely care, chronic disease management, and reducing indirect losses associated with avoidable illness, disability, and productivity decline. The economic effect of digitalization depends on data quality, interoperability, stable financing, digital competencies, organizational readiness, cybersecurity, and personal medical data protection.